2014
DOI: 10.1530/jme-14-0092
|View full text |Cite
|
Sign up to set email alerts
|

In vivo oestrogenic modulation of Egr1 and Pitx1 gene expression in female rat pituitary gland

Abstract: EGR1 and PITX1 are transcription factors required for gonadotroph cell Lhb promoter activation. To determine changes in Egr1 and Pitx1 mRNA levels in central and peripheral pituitary stimulations, an in vivo model based on i.c.v. pulsatile (1 pulse/0.5 h over 2 h) GnRH agonist (1.5 nM buserelin) or antagonist (2 nM antide) microinjections was used. The microinjections were given to ovariectomised and 17b-oestradiol (E 2 ) (3!20 mg), ERA (ESR1) agonist propyl pyrazole triol (PPT) (3!0.5 mg), ERB (ESR2) agonist … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…It has also been demonstrated that the level of PITX1 is correlated with patient survival; patients with higher PITX1 levels exhibit a longer median overall survival in human osteosarcoma (24). The reduced expression of PITX1 is also independently correlated with shorter patient survival and may serve as a prognostic marker in colorectal carcinoma (32). In a previous study (29), it was revealed that the expression of PITX1 is decreased in GC tissues and that the increased expression of PITX1 significantly suppresses the proliferation of GC cells and tumorigenesis in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…It has also been demonstrated that the level of PITX1 is correlated with patient survival; patients with higher PITX1 levels exhibit a longer median overall survival in human osteosarcoma (24). The reduced expression of PITX1 is also independently correlated with shorter patient survival and may serve as a prognostic marker in colorectal carcinoma (32). In a previous study (29), it was revealed that the expression of PITX1 is decreased in GC tissues and that the increased expression of PITX1 significantly suppresses the proliferation of GC cells and tumorigenesis in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…We also found that lncRNA MSTRG.8143.5, which was upregulated at the follicular phase, simultaneously targeted DLL1 , EGR1 , GH1 , DUSP1 and NTRK2 in the sheep pituitary gland. The early-growth-response ( EGR1 ) gene resides within the GnRH transcriptional network and belongs to the primary-response-gene family [ 43 ]. The detectable changes in EGR1 transcription occur as early as possible within 1 h of GnRH stimulation [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in silico analysis in combination with the BMP15 promoter sequence showed that the -14 to -8 bp region of the BMP15 promoter is the primary regulatory target for the pituitary homebox 1 protein (PITX1) (49), in which two of the active binding regions were validated in vitro, namely, prom-G and prom-C constructs. PITX1 was reported to be associated with gonadotroph cell activation and estrogenic signals (58), and the estrus cycle-related estrogen signaling pathway was positively involved in POF traditional Chinese medicine treatment (59). Despite recent findings demonstrating the involvement of BMP15 mutation in POF, further studies elucidating the roles of modulators would lead to a better understanding of the disease pathogenesis.…”
Section: Bone Morphogenetic Protein 15 (Bmp15)mentioning
confidence: 99%